Elongation factor G bound to the ribosome in an intermediate state of translocation - Tourigny, David S. (2013)
A key step of translation by the ribosome is translocation, which involves the movement of mRNA and tRNA with respect to the ribosome. This allows a new round of protein chain elongation by placing the next mRNA codon in the A site of the 30S subunit. Translocation proceeds via an intermediate state in which the acceptor ends of the tRNAs have moved with respect to the 50S subunit but not the 30S subunit, to form hybrid states. The GTPase elongation factor G (EF-G) catalyzes the subsequent movement of mRNA and tRNA with respect to the 30S subunit. Here we present a crystal structure at 3 Å resolution of the Thermus thermophilus ribosome with a tRNA in the hybrid P/E state bound to EF-G with a GTP analog. The structure provides insights into structural changes that facilitate translocation and suggests a common GTPase mechanism for EF-G and elongation factor Tu.